Prospects for the development of FoodTech in modern realities in Russia - V. M. Tiunov (Современная наука и инновации, 2023)
This article discusses the prospects for the development of Foodtech in the Russian Federation. Currently, digital technologies are the main driver of growth and a condition for the modernization of the catering sector. The coronavirus infection (COVID-19), which appeared in 2020, served as a huge impetus for the introduction of digital technologies to enterprises. It has been established that the following technologies have received the greatest development: the development of high-tech packages, the development and implementation of "SMART" devices and applications, food delivery services (FoodDelivery), pre-order of ready-made food (Take-Away), including the delivery of products from supermarkets (Online Grocery), which for this period of time are in great demand demand, and have a huge potential for development. One of the main places for food companies through which they are able to provide their goods and find a paying audience are marketplaces. Undoubtedly, the main advantages of marketplaces are: their growing availability, global scale, as well as improving supply chains. At the same time, the author found that complete dependence on marketplaces can lead to some factors that in the long term can negatively affect enterprises. Recommendations for leveling these factors are given. Significant directions were also highlighted that can lead to a powerful push for the promotion of digital technologies in the field of public catering.